OPHTHALMOLOGICAL EVALUATION OF SHEEP FROM THE ALENTEJO REGION - PORTUGAL - Guimarães, Tarcísio Guerra; Cardoso, Karla Menezes; Haddade, Ismail Ramalho; Brito, Marta Marques; Oliveira, Manuela Melo; Mamede, Fabricio Villela; Pimenta, Paulo; Alexandre, Nuno Miguel Lourenço (Archives of Veterinary Science, 2022)
Considering the importance of the flock of Alentejo sheep, the goal of this study was to determine the average values of eye examinations, evaluate the ophthalmoscopic features and fluorescein staining for Merino sheep from Alentejo region, in Portugal. The 48 eyes of 24 healthy, female sheep belonging to the sheep flock at the University of Évora were evaluated. The average values obtained for Schirmer tear test (STT) were 19.0 ± 5.22 mm/min, with a reduction of tear production varying according to the age of the animal, for tear pH were 7.7 ± 0.48 and for intraocular pressure (IOP) was 12.7 ± 3.03 mmHg. Fundus aspects were observed in the tapetal area with shades of blue, green and yellow. The optic disc was predominantly in the transition area between tapetal and non-tapetal regions of elliptical shape, with holoangiotic vascular pattern. None of the animals showed fluorescein staining on the ocular surface. In the context of the investigation, these data may be useful to improve the clinical approach to the species and reference standards of the exam’s values